170 keV Proton radiation effects on low-frequency noise of bipolar junction transistors. Issue 3 (3rd April 2017) - Yue, Long; Yang, Shaohua; Liu, Yuan; Zhang, Zhangan; Li, Xingji; He, Yujuan; Lei, Zhifeng; Lu, Yudong; En, Yunfei
ABSTRACT: In this paper, the electrical properties and low-frequency noise for bipolar junction transistors irradiated by 170 keV proton are examined. The result indicates that for the sample under proton irradiation with fluence 1.25 × 10 14  p/cm 2, base current I B in low bias range ( V BE < 0.7 V) increases due to superimposition of radiation-induced recombination current, while the gain decreases significantly. Meanwhile, the low-frequency noise increases in the proton-irradiated sample. By analysis of evolution of parameters extracted from low-frequency noise power spectra, it is demonstrated that radiation-induced noise is mainly originated from carrier fluctuation modulated by generation–recombination centers (G–R centers) located at the interface of Si/SiO2, which are introduced by proton-radiation-induced defects. It is also confirmed that the electrical properties and noise behavior of irradiated sample are mostly affected by the carrier recombination process caused by G–R centers at the interface of Si/SiO2 than by G–R centers in EB junctions.